Geese and grazing lawns: responses of the grass Festuca rubra to defoliation in a subarctic coastal marsh - O, P. C.; Kotanen, P. M.; Abraham, K. F. (Canadian Journal of Botany, 2006)
In coastal marshes on James Bay and southern Hudson Bay, Canada, the grass Festuca rubra L. is heavily used for forage by both Snow (Chen caerulescens caerulescens (Linnaeus)) and Canada Geese ( Branta canadensis (Linnaeus)). On Akimiski Island, James Bay, this grass occurs in a mosaic of short, heavily grazed patches and tall, lightly grazed patches. We investigated whether short plants are primarily a plastic morphological response to grazing by geese. Over two growing seasons, we measured growth of short patches protected from grazing and of tall patches subjected to mowing treatments, with unmanipulated short and tall controls. Protection resulted in rapid conversion from a short growth form to a tall form, similar in height and biomass to plants in tall control plots. Mowed tall plants also rapidly recovered to near tall control values for height and biomass. A single 3 week treatment episode often permitted nearly full recovery to tall form. In some cases, more sustained protection was required, but repeated mowing ultimately may have reduced growth rates. These results indicate that the morphology of individual plants of Festuca rubra plastically recovers from changes in defoliation pressure. Consequently, short patches likely represent grazing lawns maintained by intensive foraging by geese.